Etkili parlamenter muhalefetin anayasal esasları - Özkan, Seda (My University, 2023)
Bu çalışmanın amacı, 1982 Anayasası döneminde Türkiye Büyük Millet Meclisinin 22’nci-27’nci Yasama Dönemleri süresince parlamenter muhalefetin etkililiğini saptamaktır. Üç bölümden oluşan bu çalışmanın birinci bölümünde, kavramsal ve kuramsal boyutuyla ele alınan muhalif edimsellik, siyasal muhalefetin biçimleri ve parlamenter muhalefet konularının yanı sıra parlamenter muhalefetin işlevleri ve araçları da belirlenmektedir. Çalışmanın ikinci bölümünde, Türkiye’de iktidar-muhalefet ilişkisi bağlamında 1982 Anayasası ve Türkiye Büyük Millet Meclisi İçtüzüğü incelenerek bu çerçevede parlamenter muhalefet olgusuna ilişkin teorik tespitler niteliksel olarak analiz edilmektedir. Bu bağlamda 1982 Anayasası’nda parlamenter muhalefetin alanını belirleyen maddeler ve Anayasa’nın 98’inci maddesi uyarınca Türkiye Büyük Millet Meclisi üyesi parlamenterlerce kullanılan parlamenter denetim araçları incelenmektedir. Ayrıca Türkiye Büyük Millet Meclisi İçtüzüğünde parlamenter muhalefetin başvurduğu muhalefet araçları ile yine İçtüzükte düzenlenen disiplin cezalarına yönelik hükümler de ayrıntılı olarak ele alınmaktadır. Çalışmanın üçüncü bölümünde, 1982 Anayasası döneminde 22’nci-27’nci Yasama Dönemleri süresince parlamenter muhalefetin, denetim araçlarını kullanmada gösterdiği etkinlik kapasitesi niceliksel olarak analiz edilmektedir.

This thesis aims to determine the effectiveness of parliamentary opposition during the 22nd-27th legislative periods of the Grand National Assembly of Turkey in the 1982 Constitution of the Republic of Turkey. The thesis consists of three chapters. In the first chapter, oppositional performativity, forms of political opposition and parliamentary opposition are examined conceptually and theoretically, and functions and tools of parliamentary opposition are determined. In the second chapter, in context of the government-parliamentary opposition relationship in Turkey, the 1982 Constitution of the Republic of Turkey and the Rules of Procedure of the Grand National Assembly of Turkey are examined. In this chapter of the thesis, theoretical determinations on phenomenon of parliamentary opposition are qualitatively analyzed within the framework of the 1982 Constitution of the Republic of Turkey and the Rules of Procedure of the Grand National Assembly of Turkey. In this context, articles determining the scope of parliamentary opposition in the 1982 Constitution of the Republic of Turkey and parliamentary oversight tools used by the members of the Grand National Assembly of Turkey pursuant to Article 98 of the 1982 Constitution of the Republic of Turkey are discussed. In addition to parliamentary opposition tools used by the opposition in the Rules of Procedure of the Grand National Assembly of Turkey and parliamentary procedures for disciplining are detailed. In the third chapter, the parliamentary opposition’s effective capacity in using oversight tools during the 22nd-27th legislative periods of the 1982 Constitution of the Republic of Turkey is analyzed quantitatively.
Constitutional principles of effective parliamentary opposition
Keywords: Anayasa hukuku; Constitional law; Denetim araçları; Legislative oversight; Muhalefet; Muhalefet (Siyasal bilim); Muhalif edimsellik; Opposition; Opposition (Political science); Oppositional performativity; Oversight tools; Parlamenter muhalefet; Parlamenter muhalefet araçları; Parliamentary opposition; Parliamentary opposition tools; Political opposition; Politics and administration; Siyasal muhalefet; Siyaset ve yönetim; Turkey; Türkiye; Yasama denetimi